Clinical practice and adherence to the diagnosis and treatment of NMIBC guidelines: a report of a recognition based clinical cases study. Issue 1 (January 2015) - Torreggiani, Aldo; Colombo, Renzo; Gontero, Paolo; Lapini, Alberto; Sanseverino, Roberto; Serretta, Vincenzo
For non-muscle invasive bladder cancer, a disease with a considerable epidemiological and socio-economic impact, the introduction of the Guidelines has always evoked as a tool for the resolution of long-standing disputes in terms of diagnosis and therapy. Check the degree of routine clinical practice adherence to the Recommendations is for this disease, more than for other uro-oncology pathology, an urgent need felt by the urological community. To assess the level of Guidelines adherence's, and study issues related to the paths of diagnosis and treatment of non-muscle invasive bladder cancer, and identifying the processes actually implemented in daily clinical practice, a series of case studies has submitted to a group of experts. The acknowledgement study allowed testing the impact of the current Evidence Based Medicine Recommendations in the everyday clinical practice identifying strengths and weaknesses. Questions Responses Analysis' of 5 clinical cases (Ta low grade, T1 low grade, T1 high grade, T1 high grade + CIS, Ta low-grade multiple recurrence) showed a moderate amendment to the European Association of Urology (EAU)-Guidelines. On the other hand, it was emphasized that there are clear discrepancies between what should be done, in accordance with the Evidence Based Medicine Recommendations, and what is actually do in everyday clinical practice. The most common reason for the low Recommendations adherences are structural and organizational practical limitations.